2014
DOI: 10.1039/c4gc00794h
|View full text |Cite
|
Sign up to set email alerts
|

An efficient and stable star-shaped plasticizer for starch: cyclic phosphazene with hydrogen bonding aminoethoxy ethanol side chains

Abstract: The combination of starch and a star-shaped non-hazardous plasticizer based on phosphazene produces self-reinforced composite films with temporal stability, no leaching and no retrodegradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 70 publications
1
16
0
Order By: Relevance
“…However, small‐molecule plasticizers usually evaporate during melt processing and also have a strong tendency to migrate toward the surface during storage . The addition of a small‐molecule plasticizer to starch may decrease its melting temperature ( T m ), but the limited mechanical properties, higher moisture sensitivity, and release of small‐molecule plasticizer from matrix are also the main challenges in its applications . The common way to reduce the migration and evaporation of plasticizers is to increase the molecular mass of the plasticizer to an upper limit where migration will be minimized and the miscibility with the matrix will still be retained …”
Section: Introductionmentioning
confidence: 99%
“…However, small‐molecule plasticizers usually evaporate during melt processing and also have a strong tendency to migrate toward the surface during storage . The addition of a small‐molecule plasticizer to starch may decrease its melting temperature ( T m ), but the limited mechanical properties, higher moisture sensitivity, and release of small‐molecule plasticizer from matrix are also the main challenges in its applications . The common way to reduce the migration and evaporation of plasticizers is to increase the molecular mass of the plasticizer to an upper limit where migration will be minimized and the miscibility with the matrix will still be retained …”
Section: Introductionmentioning
confidence: 99%
“…10 In addition, HBPET has better compatibility with resins or starch 11,12 and resistance to migration in a polymer matrix than small polar molecules. 13 Our group found that hyperbranched poly(citrate glyceride) not only had good plasticizing effect and resistance to migration in starch, but also could inhibit the moisture absorption of starch. 9 There are two common methods for the preparation of HBPET.…”
Section: Introductionmentioning
confidence: 93%
“…Hyperbranched polyester (HBPET) is a kind of polymer with branched chains and multifunctional groups, which can be used as a polymer plasticizer . In addition, HBPET has better compatibility with resins or starch and resistance to migration in a polymer matrix than small polar molecules . Our group found that hyperbranched poly(citrate glyceride) not only had good plasticizing effect and resistance to migration in starch, but also could inhibit the moisture absorption of starch …”
Section: Introductionmentioning
confidence: 98%
“…The synthesis of HDPCP was according to the procedure literature, 32 as illustrated in Scheme 1. A four-necked glass reactor equipped with thermometer, mechanical stirrer, condenser tube, and nitrogen inlet, 1.05 g (6.0 mmol) HCCP and 500 mL THF were added at room temperature.…”
Section: Synthesis Of Hexa-[2-(2-hydroxy-ethoxy)-ethylamino]cyclotripmentioning
confidence: 99%